Professional development in environmental education in Zanzibar, Tanzania: distances encountered in a semi-distance learning course - Heylings, Phillippa Frances (Rhodes University, Faculty of Education, Department of Education, 2000)
In Zanzibar, in 1995, opportunities for professional development in environmental education were minimal. Yet the demand for professional development was high, especially because of an emphasis on formal qualifications in the country. Credibility was afforded to forms of professional development, aimed at creating more 'experts'. Ongoing environmental education practice was not achieving its objectives. Into this setting, which was culturally and socio-politically different from the South African context where it was developed, I introduced the Rhodes University Certificate and Gold Fields Participatory Course in Environmental Education (RU/GF); a non-formal, counter-hegemonic course which encouraged critical reflection on the dominant orientations to environmental education practice "“ including professional development. I used critical ethnographic and action research methods to explore my praxiological interest, the adaptation of the RU/GF curriculum to the Zanzibar context. During the research process, a decision was made to formally accredit the RU/GF course. This decision did not alter the course orientation or the learning process but opened up possibilities for future curriculum development processes. It allowed the students both a formal qualification necessary for status and promotion, and participation in a learning process that challenged the dominant paradigm on professional development and status from within the socio-political context. The research took on a reflexive orientation to research and environmental education. Through a dialectical development of theory, method and results, several important issues emerged. These deal with the 'distances' encountered in attempting to address some of the perceived dichotomies in professional development in environmental education through semi-distance learning: the distances between status and learning; the need for career upgrading and the type of learning considered appropriate for professional development in environmental education; the non-quantifiable aims associated with a reflexive orientation to professional development and formal assessment demands for measurable criteria; the democratisation of open-entry courses and the elitism of restricted access; the focus on individual growth and the attainment of a normative grade; theory and practice; and finally distances between learner, text and language. The research supports similar findings emerging from evaluation of the RU/GF course in South Africa and resonates with, and contributes to, issues concerning professional development in environmental education being considered internationally.
Keywords: Environmental education -- Tanzania -- Zanzibar; Distance education -- Tanzania -- Zanzibar; Environmental education; Distance education